1990
DOI: 10.1080/03014223.1990.10422591
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic control of larval development rate inPlanotortrix excessana(Lepidoptera: Tortricidae): Evidence for larval diapause

Abstract: The larval development rate and pupal weights of Planotortrix excessana Walker were monitored under seven different 24 h photoperiods. Larvae developed through 5-7 instal's with the extra instars being most common in females. Photoperiod had a significant effect on the duration of all instars, total larval period, and number of instars.The response for both larval duration and instar number was typical of insects in which diapause occurs during long days. Evidence for the presence of a photoperiodically induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1990
1990
1991
1991

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…Earlier studies on the New Zealand tortricid Planotortrix octo Dugdale have shown a photoperiodic response for larval duration and instar number, with larvae taking longer to develop and expressing a supernumerary 6th or 7th instar under short days (Morris 1990a). The shape of the response curve is similar to that found in long-day diapausing insects (Beck 1980).…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Earlier studies on the New Zealand tortricid Planotortrix octo Dugdale have shown a photoperiodic response for larval duration and instar number, with larvae taking longer to develop and expressing a supernumerary 6th or 7th instar under short days (Morris 1990a). The shape of the response curve is similar to that found in long-day diapausing insects (Beck 1980).…”
Section: Introductionsupporting
confidence: 61%
“…The size of instars 1,3, and 6 are not recorded as tbe photoperiodic differences were not significant. However, tbese are recorded in a earlier paper, and tbe difference in head-capsule size between tbe 5 and 6 instar groups is statistically significant from tbe 3rd instar onwards (Morris 1990a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of these are high during shortdays, with a sharp decline at long day photoperiods and a shallower decline in total darkness (Morris 1990a).…”
Section: Introductionmentioning
confidence: 99%